Cytogenetic analysis detects presence of Riverine, Swamp and their hybrid buffaloes in North-east India - B. Prakash,; Mishra, B.P.; Kataria, R.S.; Das, G.C. (Journal of Livestock Biodiversity, 2025)
There is still not a settled view about the centre of domestication of buffaloes. Different workers have proposed different centres of domestication including western India, south-east China or South China. North eastern part of India constitutes the dividing line of these proposed centres of domestication of buffaloes. We, thus, presumed that this region should form the dividing boundary between domesticated riverine buffaloes and semi-domesticated swamp buffaloes. A total of 158 representative buffaloes belonging to six different regions of North East India i.e. Assamese-upper (Brahmaputra valley, 46), Assamese-Lower (Silchar, 18), Assamese-North (Dibrugarh, 26) Nagaland (12), Manipur (40) and Mizoram (16) were evaluated cytogenetically to ascertain their riverine/swamp status. The results revealed the existence of domesticated forms of all varieties of water buffalo i.e. river, swamp and river X swamp hybrid types in close geographic proximity. Of the six buffalo populations investigated in the study, one was predominantly pure riverine (upper-Assamese), four were pure swamp (Assamese-North, Manipuri, Nagaland and Mizo) and one was significantly hybrid (44.4%) of river X swamp (Lower- Assamese). The north-east region of India, thus, constitutes the demarcation line between swamp (inhabitants of south- eastern countries) and riverine (Major buffalo populations of India, Pakistan, Sri-Lanka, etc.) buffaloes.